Discriminating power of rapidly mutating Y-STRs in deep rooted endogamous pedigrees from Sindhi population of Pakistan. (September 2018) - Rakha, Allah; Oh, Yu Na; Lee, Hwan Young; Hussain, Safdar; Waryah, Ali Muhammad; Adnan, Atif; Shin, Kyoung-Jin
Highlights: We analyzed 13 RM Y-STRs in 216 pairs, 1–7 generations pedigrees from Sindh, Pakistan. Mutations were frequently observed at DYF399S1, DYS518, DYS449, DYS547 and DYF403S1b2. Differentiation rate with RM Y STRs exceeds to 32.87%, while with PPY23 and Yfiler remain 6.85% and 3.65% respectively. Abstract: Rapidly mutating Y-STRs (RM Y-STRs) have been paid much attention in recent years. The 13 RM Y-STRs (DYF387S1, DYF399S1, DYF403S1a/b, DYF404S1, DYS449, DYS518, DYS526I/II, DYS547, DYS570, DYS576, DYS612, DYS626, and DYS627) have been proved to have substantially higher haplotype diversity and discrimination capacity than conventionally used Y-STRs indicating the considerable power in paternal lineage differentiation in endogamous populations, separation of which is usually impossible with standard Y-STRs. In current study, we analyzed the RM Y-STRs and PowerPlex® Y23 System in 216 male relatives from 18 deep rooted endogamous Sindhi families from Pakistan. Mutations were frequently observed at DYF399S1, DYS449, DYS518DYS547 and DYF403S1b2 loci, which are known to mutate more rapidly than other RM Y-STRs. Overall differentiation rate with RM Y-STRs was as high as 32.88%, while those with PowerPlex® Y23 System and AmpFℓSTR® Yfiler™ kit were 6.85% and 3.65% respectively. The differentiation rate of RM Y-STRs was 29.22% and 26.03% higher than those of AmpFlSTR® Yfiler™ kit and PowerPlex® Y23 System, respectively.